(untitled) (Scientia Agropecuaria, 2025)
Typically, the transition zone of quaternary and tertiary volcanoes is a potential area for agricultural development but is prone to landslides. Landslide occurrences and the use of former landslide zones exhibit a distinct soil organic carbon (SOC) distribution, necessitating analysis to sustain agricultural output. Laboratory SOC measurements on landscape size are not expedient, necessitating the development of an estimating method for representation. This study aims to analyze the relationship between relief and SOC using LiDAR (Light Detection and Ranging) data. LiDAR acquisition was carried out to identify relief units as units of analysis. Soil sample measurements were carried out in the laboratory with the parameters analyzed including pH, Bulk Density, Moisture Content, Organic Carbon, Organic Matter, N-total, CN Ratio and Cation Exchange Capacity. The results showed that SOC and relief had R2 = 0.89 in the upper layer (0 – 20 cm) and 0.86 in the lower layer (20 - 40 cm). Relief has a high correlation with soil characteristics at the top and bottom of soil depths. It is because of relatively stable elevation and relatively dynamic land cover that SOC is spread out in a clustered way. This research can be used as a basis for agricultural land management, especially in areas prone to landslides.